Hedge accounting com derivativos exóticos e tributação - Julião, Márcio dos Santos (2011)
This research examined the application of the hedge accounting methodology for derivatives and its object o f protection. It was shown the fair v alue calculation, marketto-market value, hedge effectiveness test, documentation and accounting classification in the fair value hedge and cash flow hedge models. It was also verified the impact of taxes on the hedge effectiveness.